2021
DOI: 10.1111/all.14828
|View full text |Cite
|
Sign up to set email alerts
|

Markers for the involvement of endothelial cells and the coagulation system in chronic urticaria: A systematic review

Abstract: Chronic urticaria (CU) is a chronic inflammatory skin disorder for which different pathogenic mechanisms have been described. CU is characterized by the activation of skin mast cells (MCs) with subsequent degranulation and the release of histamine and other pro-inflammatory mediators. As a result, the endothelium gets activated resulting in vasodilation and extravasation, clinically visible as erythema and itchy wheals and/or angioedema, respectively. 1 These symptoms of CU develop recurrently and resolve spon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 122 publications
0
33
2
1
Order By: Relevance
“…Other issues that were not considered that are important for conclusions about previous studies are the study population size, the inclusion of historic or concurrent controls, the use of validated assays and whether the results were confounded by treatment regimens. In addition to lessons learned from this review by Montmans et al, other proofs of the involvement of the coagulation cascade in urticaria include reports showing the beneficial effect of anticoagulants (e.g., heparin, warfarin, nadroparin) in patients with refractory urticaria or unresponsive to antihistamines, and reports showing that the plasma levels of Ddimer can predict clinical response to therapy with antihistamines or anti-IgE monoclonal antibody (1,5). What remains debatable is whether IgE antibodies against tissue factor with concomitant dysfunction of the endothelial cell-mediated thrombomodulin/protein C anticoagulant pathway plays a major role in the mechanism of coagulation activation in urticaria patients (5).…”
Section: To the Editormentioning
confidence: 87%
See 1 more Smart Citation
“…Other issues that were not considered that are important for conclusions about previous studies are the study population size, the inclusion of historic or concurrent controls, the use of validated assays and whether the results were confounded by treatment regimens. In addition to lessons learned from this review by Montmans et al, other proofs of the involvement of the coagulation cascade in urticaria include reports showing the beneficial effect of anticoagulants (e.g., heparin, warfarin, nadroparin) in patients with refractory urticaria or unresponsive to antihistamines, and reports showing that the plasma levels of Ddimer can predict clinical response to therapy with antihistamines or anti-IgE monoclonal antibody (1,5). What remains debatable is whether IgE antibodies against tissue factor with concomitant dysfunction of the endothelial cell-mediated thrombomodulin/protein C anticoagulant pathway plays a major role in the mechanism of coagulation activation in urticaria patients (5).…”
Section: To the Editormentioning
confidence: 87%
“…We read with much interest the review article recently published by Mostmans et al (1). The work is an excellent compilation of studies on alterations of vascular endothelial cell-associated molecules and coagulation factors in urticaria.…”
Section: To the Editormentioning
confidence: 99%
“…The majority of coagulation factors are produced in the liver; to prevent the effects of hepatopathy on the levels of the coagulation factors and the corresponding tests, we enrolled normal controls and patients whose liver function tests were normal. Interestingly, factors including FVIII and vWF (which act as markers of endothelial activation) ( 53 ) were produced in the endothelial cells. Investigation of the levels of these factors in COVID-19 patients revealed that their levels increased and may correlate with poorer prognosis ( 54 56 ).…”
Section: Discussionmentioning
confidence: 99%
“…Two of these inhibitory MC receptors are Siglec-8 and CD200R. 36,37 Endothelial cells (ECs) and eosinophils contribute importantly to key features of CSU. Several markers of EC activation have been reported, from adhesion molecules, tissue factor and P-selectin to D-dimers, MMP-9, endostatin, heat shock proteins, cleaved high molecular weight kininogen and adipokines.…”
Section: Definition and Burdenmentioning
confidence: 99%